Peran Intermediasi Bank Pembangunan Daerah (BPD) Terhadap Pertumbuhan Ekonomi Daerah - Berly, Berly; Mahi, Benedictus Raksaka; Mardanugraha, Eugenia (Jurnal Akuntansi dan Bisnis, 2022)
This study examines the impact of the intermediary role of 27 Regional Development Banks (RDB) on regional economic growth using county and city panel data for the 2015 – 2019 period. The test uses a fixed effect regression model with control variables of labour force participation rates, education, and local government spending. The findings of this study were the role of RDB intermediation has a significant positive effect in encouraging regional economic growth in all counties and cities. The study found that the impact of third party funds was higher if all of it disbursed into credit on the growth of real Gross Regional Domestic Product per capita. Third-party funds proven to increase capital accumulation channelled through credit, thereby encouraging economic growth. RDB has a role in reducing the obstacles to collecting funds in the district by distributing Third - party funds from the city to credit in the county. The results of the study shows that the impact of consumption and productive credit in county and city showed different results. In the county, consumer credit increases the purchasing power of households, while in the city, productive credit becomes physical capital accumulation with a higher multiplier so that it has a positive effect on economic growth. These results suggest that RDB should improve their active role in credit distribution, both in increasing the number and quality of intermediation, especially for productive use that is evenly distributed throughout the region. RDB needs to increase the capacity of lending, especially through increasing capital. Penelitian ini menguji dampak peran intermediasi 27 BPD terhadap pertumbuhan ekonomi daerah menggunakan data panel kabupaten dan kota periode tahun 2015 – 2019. Pengujian menggunakan regresi model efek tetap dengan variabel kontrol tingkat partisipasi angkatan kerja, pendidikan, dan belanja pemerintah daer ah. Hasil penelitian membuktikan peran intermediasi BPD berpengaruh positif signifikan mendorong pertumbuhan PDRB riil per kapita pada keseluruhan kabupaten dan kota. Penelitian menemukan dampak Dana Pihak Ketiga (DPK) lebih tinggi apabila seluruhnya disalurkan menjadi kredit terhadap pertumbuhan PDRB riil per kapita. DPK terbukti meningkatkan akumulasi modal yang disalurkan melalui kredit sehingga mendorong pertumbuhan ekonomi. BPD berperan mengurangi kendala penghimpunan dana di kabupaten dengan mendistribusikan DPK dari kota menjadi kredit di kabupaten. Hasil penelitian dampak kredit konsumsi dan produktif di kabupaten dan kota menunjukkan hasil berbeda. Di kabupaten kredit konsumsi meningkatkan daya beli rumah tangga, sedangkan di kota kredit produktif menjadi akumulasi modal fisik dengan multiplier lebih tinggi sehingga berpengaruh positif terhadap pertumbuhan ekonomi. Mengacu konteks pembangunan Indonesia yang masih dalam tahap perkembangan, diperlukan peran aktif penyaluran kredit BPD baik peningkatan jumlah maupun kualitas intermediasi terutama untuk penggunaan produktif yang merata di seluruh daerah. BPD perlu meningkatkan kapasitas penyaluran kredit terutama melalui peningkatan permodalan.